Effect of Damaged Starch and Wheat-Bran Arabinoxylans on Wheat Starch and Wheat Starch–Gluten Systems - Teobaldi, Andrés Gustavo (2024)
This study investigated the impact of damaged starch and arabinoxylans on the thermal and pasting behavior of mixtures containing starch and gluten. The mixtures containing starch, arabinoxylans, and gluten were dispersed in water and a 50% sucrose solution. When arabinoxylans were added to native starch in water, it did not modify the viscosity profiles. An increase in viscosity parameters was observed due to the addition of arabinoxylans to starch with a higher level of damage. Gluten did not influence the effects caused by arabinoxylans. In the sucrose solution, arabinoxylans caused an increase in the viscosity parameters of native starch and starch with higher damage content dispersions. Gluten caused greater viscosity increases when arabinoxylans were added. In water, the addition of arabinoxylans to native starch caused a decrease in the enthalpy of gelatinization and an increase in the onset temperature. Adding arabinoxylans to starch with a higher level of damage caused the opposite effects. In the presence of sucrose, arabinoxylans caused a decrease in the enthalpy of gelatinization. These results lay the foundations for studying the influence of damaged starch and arabinoxylans in water-rich systems characterized by the presence of substantial proportions of sucrose, such as batter formulations.